2004
DOI: 10.1002/cphc.200301043
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dynamics of Gas‐Phase SN2 Reactions

Abstract: Understanding the state-resolved dynamics of elementary chemical reactions involving polyatomic molecules, such as the well-known reaction mechanism of nucleophilic bimolecular substitution (SN2), is one of the principal goals in chemistry. In this Review, the progress in the quantum mechanical treatment of SN2 reactions in the gas phase is reviewed. The potential energy profile of this class of reactions is characterized by two relatively deep wells, which correspond to pre- and post-reaction chargedipole com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 130 publications
(165 reference statements)
0
43
0
Order By: Relevance
“…A possible extension of the present model would therefore be to further increase the dimensionality of the potential energy surface [32] and in the quantum dynamics. [4] There are seven additional degrees of freedom, and the question is whether any of them would have a critical effect on the calculated reaction rates. Out of the nine vibrational frequencies of the transition complex, see the Supporting information, the antisymmetric and symmetric Cl-P-Cl stretches are already included in the two-dimensional model.…”
Section: Two-dimensional Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible extension of the present model would therefore be to further increase the dimensionality of the potential energy surface [32] and in the quantum dynamics. [4] There are seven additional degrees of freedom, and the question is whether any of them would have a critical effect on the calculated reaction rates. Out of the nine vibrational frequencies of the transition complex, see the Supporting information, the antisymmetric and symmetric Cl-P-Cl stretches are already included in the two-dimensional model.…”
Section: Two-dimensional Modelmentioning
confidence: 99%
“…[1,2] Specially the nucleophilic substitution at carbon centers (S N 2@C) have been extensively studied, both theoretically and experimentally. [3,4] The gas phase substitution reaction between a halide anion and a halomethane,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bimolecular nucleophilic substitution (S N 2) reaction is the most common reaction of that type, in which a nucleophile (often negatively charged) approaches a saturated carbon from one side, displaces a leaving group on the opposite side of the carbon atom, resulting in inversion of the carbon centre. Strong solvent effects of these reactions in solution have prompted investigations of the gas-phase S N 2 reaction to probe the intrinsic reaction mechanisms without solvent123456789101112131415161718192021222324252627. Numerous experimental and theoretical studies have revealed that an inverse secondary kinetic isotope effect (KIE), that is, k H / k D <1 (where k denotes the thermal rate constant), is characteristic for a thermal S N 2 reaction when the isotopically substituted atom is not directly involved in a reaction12345678910.…”
mentioning
confidence: 99%
“…Furthermore, they found that the reaction thresholds for S N 2 reactions, which are larger than their corresponding barrier heights, result from direct reactions1517. Many reduced dimensionality quantum scattering studies were also carried out to investigate dynamics in S N 2 reactions19202122. Recently, the molecular beam experiments in the Wester's group, in combination with theory, have revealed unprecedented dynamical details on some exothermic S N 2 reactions2324252627.…”
mentioning
confidence: 99%